Evaluation of Vascular Involvement in Children with Celiac Disease - Ezgi Kıran Taşcı; Sevgin Taner; Eser Doğan; Miray Karakoyun; İpek Kaplan Bulut; Caner Kabasakal; Ertürk Levent; Funda Çetin; Sema Aydoğdu (Galenos Yayinevi, 2023)
Aim:Celiac disease is associated with an increased risk of cardiovascular disease due to inflammation and autoimmunity involved in its pathophysiology. We aimed to evaluate vascular involvement in children with celiac disease based on their augmentation index, carotid pulse wave velocity, carotid intima-media thickness, echocardiographic findings, and blood pressure.Materials and Methods:This cross-sectional and controlled study was performed at a single center between 2018 and 2019. The study population consisted of 44 patients with celiac disease who had been on a gluten-free diet for at least one year.Results:We compared celiac patients with a healthy group. While the celiac patients had significantly higher carotid intima media thickness and carotid pulse wave velocity values, there was no difference in the augmentation index values. There was no significant difference in carotid artery intimal medial thickness, augmentation index and carotid pulse wave velocity values between the diet-compliant and non-compliant groups.Conclusion:Although hypertension was not detected, arterial stiffness and carotid intima media thickness measurements were higher in the celiac disease patients compared to the healthy controls. This showed that these parameters can be used in early vascular damage assessment. These measurements, which are non-invasive and repeatable, can be a guide for the monitoring of the development of preclinical atherosclerosis in the follow-up of the pediatric patients diagnosed with celiac disease.